Nanophysical Antimicrobial Strategies: A Rational Deployment of Nanomaterials and Physical Stimulations in Combating Bacterial Infections. Issue 10 (27th January 2022) - Jia, Bingqing; Du, Xuancheng; Wang, Weijie; Qu, Yuanyuan; Liu, Xiangdong; Zhao, Mingwen; Li, Weifeng; Li, Yong‐Qiang
Abstract: The emergence of bacterial resistance due to the evolution of microbes under antibiotic selection pressure, and their ability to form biofilm, has necessitated the development of alternative antimicrobial therapeutics. Physical stimulation, as a powerful antimicrobial method to disrupt microbial structure, has been widely used in food and industrial sterilization. With advances in nanotechnology, nanophysical antimicrobial strategies (NPAS) have provided unprecedented opportunities to treat antibiotic‐resistant infections, via a combination of nanomaterials and physical stimulations. In this review, NPAS are categorized according to the modes of their physical stimulation, which include mechanical, optical, magnetic, acoustic, and electrical signals. The biomedical applications of NPAS in combating bacterial infections are systematically introduced, with a focus on their design and antimicrobial mechanisms. Current challenges and further perspectives of NPAS in the clinical treatment of bacterial infections are also summarized and discussed to highlight their potential use in clinical settings. The authors hope that this review will attract more researchers to further advance the promising field of NPAS, and provide new insights for designing powerful strategies to combat bacterial resistance. Abstract : Nanophysical antimicrobial strategies, the "beautiful and incredible" encounter between nanomaterials and physical stimulations, and their applications, as well as current challenges and further perspectives in combating bacterial infections, are systematically summarized and discussed. This review is anticipated to provide new insights into the design of powerful weapons for arduous campaigns against bacterial resistance.